1966
DOI: 10.1172/jci105315
|View full text |Cite
|
Sign up to set email alerts
|

The site of pulmonary vasomotor activity during hypoxia or serotonin administration.

Abstract: Pulmonary arterial pressure increases in dogs exposed to alveolar hypoxia or intravascular infusion of 5-hydroxytryptamine (serotonin). Although most investigators believe that this increase in pressure reflects a vasoconstriction in the pulmonary vascular bed, the site of vasoconstriction, whether venular, capillary, or arteriolar, is controversial. Interpretations have been based previously upon measurements of pressure and flow at various sites in the pulmonary circulation and have been handicapped by the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1967
1967
1989
1989

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Several studies have shown venous constriction (14,15), whereas others have found predominant arterial constriction (16,17). Our findings help explain many of the seemingly conflicting results in the literature.…”
Section: Methodssupporting
confidence: 60%
“…Several studies have shown venous constriction (14,15), whereas others have found predominant arterial constriction (16,17). Our findings help explain many of the seemingly conflicting results in the literature.…”
Section: Methodssupporting
confidence: 60%
“…Introduction 5-Hydroxytryptamine (serotonin) contracts canine and human isolated intrapulmonary vascular preparations (1)(2)(3)(4) and elevates pulmonary vascular resistance in intact organisms (5)(6)(7)(8)(9)(10) or vascularly isolated perfused lungs (1 1-13). Microembolization or in situ aggregation of platelets produces an elevation of pulmonary vascular resistance, leading to pulmonary hypertension, which can be attributed in part to the release of vasoactive substances (5,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…9). It is apparent from the most recent reviews (13,14) that the sites of action for alveolar hypoxia, histamine (15), and serotonin (16,17) are very much in doubt.…”
mentioning
confidence: 99%